The Relationship Between Education Funding and Student Performance in Unity Schools in Nigeria - Elizabeth Hassan; Wim Groot; Louis Volante (Education Sciences)
Developing countries need to significantly increase education funding in order to meet the Sustainable Development Goal 4 (SDG 4) targets. The question remains as to whether increased funding leads to improved learning outcomes and whether allocated scarce resources are used efficiently to maximize learning outcomes. Using ordinary least squares (OLS) regression and stochastic frontier analysis (SFA), we investigate the relationship between education funding and student performance using a representative sample of secondary schools in Nigeria and analyze school efficiency in utilizing the funding (budget). The OLS analysis robustly indicates that an increase in the released budget—in real terms—is consistently associated with a higher pass rate, while the SFA shows that after controlling for past budgets the average inefficiency is approximately 47–60%. Our correlation findings support the argument for more funding to improve performance. However, the SFA shows that more can still be achieved with current levels of funding if schools become more efficient. We observe differences across school type and school geographical location, concluding that these factors also influence performance and efficiency. Future research should examine the performance and efficiency differences between all-girls schools and mixed schools, and the higher efficiency of schools in low socioeconomic status (SES) and conflict-affected states.